Concept of Educational Values for Tauhid Nation Education System Perspective - Nur Hadi (Faculty of Tarbiyah Institut Agama Islam Tribakti (IAIT) Kediri, 2019)
This study aims to 1) know the values ​​of Tawhid Education in the National Education System. 2) knowing the relevance of the National Education System Law No. 20 of 2003 in strengthening the values ​​of Tawhid Education. This type of research is a literature study literature (library research). The primary source of this research uses Law No. 20 of 2003 concerning the National Education System. The research results obtained 1) Tawhid education values ​​contained in Chapter II Article 3, Chapter V Article 12 paragraph 1 point A, Chapter X Article 36 paragraph 3 point A, and 2) Relevance of the National Education System Law No 20 of 2003 to strengthening the values ​​of Tawheed education that the main purpose is: